2015
DOI: 10.1002/2015gc005929
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative estimates of Asian dust input to the western Philippine Sea in the mid‐late Quaternary and its potential significance for paleoenvironment

Abstract: We present a new high-resolution multiproxy data set of Sr-Nd isotopes, rare earth element, soluble iron, and total organic carbon data from International Marine Global Change Study Core MD06-3047 located in the western Philippine Sea. We integrate our new data with published clay mineralogy, rare earth element chemistry, thermocline depth, and d 13 C differences between benthic and planktonic foraminifera, in order to quantitatively constrain Asian dust input to the basin. We explore the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
60
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 85 publications
(314 reference statements)
5
60
0
Order By: Relevance
“…Our eolian EM2 (12 lm) does not agree with the grain size of the eolian dust in the North Pacific Ocean which shows a size mode that is slightly coarser than 2 mm, with little material coarser than 16 mm (Rea & Hovan, 1995). Such inconformity is due to the different mechanisms of eolian transportion: westerly dominated eolian dust in the North Pacific Ocean (Lim & Matsumoto, 2006;Rea & Hovan, 1995) and EAWM controlled eolian dust in the low-latitude Southeast Asia area (Qin et al, 1995;Wan et al, 2012;Xu et al, 2015).…”
Section: 1002/2017gc007247mentioning
confidence: 65%
See 4 more Smart Citations
“…Our eolian EM2 (12 lm) does not agree with the grain size of the eolian dust in the North Pacific Ocean which shows a size mode that is slightly coarser than 2 mm, with little material coarser than 16 mm (Rea & Hovan, 1995). Such inconformity is due to the different mechanisms of eolian transportion: westerly dominated eolian dust in the North Pacific Ocean (Lim & Matsumoto, 2006;Rea & Hovan, 1995) and EAWM controlled eolian dust in the low-latitude Southeast Asia area (Qin et al, 1995;Wan et al, 2012;Xu et al, 2015).…”
Section: 1002/2017gc007247mentioning
confidence: 65%
“…For the mechanism of dust transport, backward trajectory analyses has shown that the particles transported to the Benham Rise can be traced back to the East Asian deserts (Jiang et al, 2013). Previous studies have shown that 10-50% (average 35%) of the terrigenous materials on the Benham Rise sediments is comprised of East Asian dust (Jiang et al, 2013;Xu et al, 2015), which is comparable with the proportion of EM2 (average 40%). In the South China Sea, EMA of detrital grain-size composition in ODP Sites 1146 and 1144 suggest that the intermediate end-member is primarily an eolian population with a diameter of about 9-11 lm, whereas the fine (about 2-5 lm) and coarse (about 19-25 lm) end-members are associated with fluvial inputs (Boulay et al, 2007;Wan et al, 2007).…”
Section: 1002/2017gc007247mentioning
confidence: 96%
See 3 more Smart Citations